PROPERTY ACCOUNTS FOR MUNICIPALITIES. - Hackett, Robert P. (The Accounting Review, 1937)
The article discusses the municipal accounting system in which fixed assets of a municipality are not used in utility operation. There are some practical reasons for the existence of this situation. These are discussed under the heads of municipal credit, depreciating value, and replacement. When a major fixed asset is acquired by a municipality it is usually financed through a bond issue. The security for these bonds is most often the general credit of the city. The financial condition of the city at the time of issuing the bonds, during the life of the bonds, and at the time of payment of the bonds, is not dependent upon the value of the fixed asset involved. In other words, from the financing point of view, there is nothing which causes the municipal officials, bondholders, or general public to need property accounts. Municipalities should keep fixed property accounts for the sake of control, historic value, and completeness, and these property accounts should be kept in a separate set of balanced accounts to preserve their unity, and to maintain the fundamental purpose of other funds already in existence.